Математическое моделирование процессов теплового и химического загрязнения производственных помещений при авариях - Беляева, Виктория Витальевна; Смалий, Дмитрий Юрьевич (НТУ "ХПИ", 2017)
Предложены методы расчета вентиляции помещений в случае аварийного выброса химических загрязнений, а также после горения огненного шара. Методы основаны на численном интегрировании трехмерного уравнения энергии и двухмерного уравнения переноса примеси в воздушной среде. Поле скорости воздушного потока рассчитывается путем численного интегрирования трехмерного уравнения потенциального течения и двухмерной модели отрывных течений невязкой жидкости. Приводятся результаты численного эксперимента.

The purpose of this scientific paper was to create numerical models and develop the methods on their basis for computation of the chemical and thermal pollution of air inside industrial premises when the failure occurs; these also allow us to analyze the chemical and thermal pollution taking into account those weighty factors that affect this process. To simulate thermal pollution of air inside the premises we use the energy equation. To describe the chemical pollution of air we use 2D model that enables the computation of the migration of pollution agent inside the premises. To solve this problem we use the space width-averaged equation of a gradient type. The air flow rate field inside the premises induced by the working ventilation is calculated on assumption that the migration of air inside the premises is potential. The numerical integration of the equation for the velocity potential and Poisson equation is conducted using A. V. Samarskii alternatively triangle method. For numerical integration of the impurity transfer equation, the energy equation and the turbulence transfer equation alter-natively-triangle implicit difference diagrams are used. Each difference equation corresponds to the record of balance ratio for the reference volume (the difference cell). The unknown value is calculated at each step using the explicit formula of point-to-point computation. This scientific paper gives constructed computer models and the efficient methods developed on their basis that are used for computation of the thermal and chemical pollution inside industrial premises in case of anthropogenic accidents. Developed computation methods allow the numerical model to take into account any arrangement and any shape of the process equipment and the position of air inlets and outlets.
Mathematical simulation of the processes of thermal and chemical pollution inside industrial premises in case of emergency situation
Keywords: аварийная ситуация; токсичное вещество; огненный шар; уравнение переноса примеси; toxic substance; impurity transfer equation